Primary tumor location (right versus left side of the colon) and resection affect the survival of patients with liver metastases from colonic neuroendocrine carcinoma: a population-based study. (September 2021) - Cai, Wen; Ge, Weiting; Zhang, Jiawei; Xie, Siyuan; Wu, Dehao; Hu, Hanguang; Mao, Jianshan
Background: Colonic neuroendocrine carcinomas (co-NECs) are heterogeneous and aggressive, especially with regard to metastasis. Whether co-NECs on the right and left sides of the colon have different characteristics from colon adenocarcinoma is unknown. Methods: The co-NEC patients were selected from the 2010–2017 Surveillance, Epidemiology, and End Results Program (SEER) database. The right and left sides of the colon were separated by the splenic flexure. Coarsened exact matching (CEM) was performed to adjust for relevant factors before regression models were constructed. Results: A total of 669 pathologically diagnosed co-NEC patients with sufficient baseline data were identified from the SEER database. A total of 80.72% of the patients had co-NEC that originated from the right side of the colon, and their mean overall survival (mOS) was similar to that of the patients with left-sided co-NECs (right versus left: 22.30 m versus 22.55 m). A total of 44.84% of the patients were diagnosed with liver metastasis (46.68% right side versus 37.98% left side). In patients with liver metastasis, those with right-sided co-NECs had better survival than those with left-sided co-NECs (mOS right versus left: 15.37 m versus 9.62 m; adjusted hazard ratio (HR) = 0.69, 95% confidence interval (CI): 0.49–0.98, p = 0.035). To further investigate the survival benefits of primary site resection, we separated the patients who had liver metastasis according to the primary site and performed CEM to balance the groups (no patients underwent liver metastasis resection or intervention). The results suggested that primary surgery could benefit patients with both left- and right-sided co-NECs (adjusted HR = 0.50, 95% CI: 0.33–0.77, p = 0.001 on the right side; HR = 0.38, 95% CI: 0.16–0.89, p = 0.026 on the left side). Conclusions: Co-NECs frequently originate on the right side and commonly develop liver metastasis. Right-sided co-NECs are associated with better survival than left-sided co-NECs after liver metastasis has occurred. Primary site resection is associated with prolonged survival in co-NEC patients with liver metastasis, regardless of the side from which the co-NEC has originated.